Oxygen saturation through pulse oximetry in sportswomen - Martín Escudero, Pilar; Miguel-Tobal, Francisco; Dotor Castilla, María Luisa; López-Silva, Sonnia María; Giannetti, Romano; Galindo Canales, Mercedes (My University, 2018)
Oximetry is a method used to assess peripheral blood oxygen saturation based on the determination of the level of red light absorption, directly influenced by the hemoglobin levels. Most studies on pulse oximetry, within the scope of sports medicine and clinic, have been performed in male populations, with few studies in female populations. The objective of our study was to determine transcutaneous oxygen saturation in sportswomen of different races and to analyze the correlation of this determination with the first (VT1) and second (VT2) ventilatory thresholds.